Growth and Survival Rate of Cyprinus carpio Linn Juvenile on Different Concentration of Regent 0.3 g Pesticide - Siti Rudiyanti; Astri Diana Ekasari (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2009)
Pesticide usage in agriculture activities which had been wasted into water environment affect to waters and organism quality. This study tried to investigate growth and survival rate of Cyprinus carpio Linn juvenile that had been exposured by pesticide and running at November 2006 – January 2007 in Center of Fish Hatchery Ungaran, Semarang. Thus, 0.7 – 0.8 gram of fishes were tested on media that contained Regent 0.3 pesticides which has fipronil 0.3% active compound. Furthermore, this study has several steps which are determination of concentration range test, definitive test to determine LC50-96 h and sublethal toxicity test. Result of determination of concentration range test showed that fipronil pesticide has low-level limit concentration 0.1 mg/L and up-level limit concentration 10 mg/L. Definitive test showed that LC50-96 h was 0.84 mg/L. Result of sublethal toxicity test showed that pesticide which has fipronil active compound with different concentrations (0.000 mg/L; 0.084 mg/L; 0.168 mg/L; 0.252 mg/L; 0.336 mg/L) significantly affect to growth and survival rate of tested fish. In addition, water quality during this study period showed that all parameters were suitable for tested fish.  Keywords: Fipronile, Cyprinus carpio juvenile, growth, survival